Emerging role of ferrous iron in bacterial growth and host–pathogen interaction: New tools for chemical (micro)biology and antibacterial therapy. (April 2021) - Gonciarz, Ryan L.; Renslo, Adam R.
Abstract: Chemical tools capable of detecting ferrous iron with oxidation-state specificity have only recently become available. Coincident with this development in chemical biology has been increased study and appreciation for the importance of ferrous iron during infection and more generally in host–pathogen interaction. Some of the recent findings are surprising and challenge long-standing assumptions about bacterial iron homeostasis and the innate immune response to infection. Here, we review these recent developments and their implications for antibacterial therapy.